Clinical evaluation of the histochemical diagnosis of Hirschsprung's disease. Issue 4 (April 1985) - Barr, L C; Booth, J; Filipe, M I; Lawson, J O
Abstract : The histochemical staining of suction rectal biopsies for acetylcholinesterase (AChE) activity is a safe and accurate diagnostic tool in the management of patients with symptoms and signs of Hirschsprung's disease. In this study 101 patients who have undergone AChE analysis of suction rectal biopsies are presented in order to correlate histochemical findings with subsequent clinical course after a minimum of 18 months follow up. There were no false positive results, but the limitations and problems associated with the technique which we have encountered are discussed. Equivocal, atypical, or negative results when contradicting clinical features are indications for repeat biopsy or full thickness biopsy, and awareness of the situations in which false negative results may occur is essential.